2005
DOI: 10.1590/s0066-782x2005001500014
|View full text |Cite
|
Sign up to set email alerts
|

Infarto fatal do miocárdio em mulher de 88 anos de idade

Abstract: An 88-year-old women sought medical care (12/29/03) complaining about a 4-hour duration epigastric pain, followed by vomiting.The patient had knowledge of her longstanding hypertension, having undergone a cerebrovascular accident two years earlier, without motive sequels. Three months before, dyspnea due to moderate exercise and lower limb edema took place. She denied syncope.Physical assessment (10/03/03) showed 68-bpm heart rate and blood pressure of 180/80 mmHg. Lung examination did not show any problems, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…No association has been described between the size of the infarction and the risk of rupture; and it is not unusual for the infarction to be small. Data collected at the Laboratory of Pathology of the Heart Institute (InCor) 20 in cases of necropsy have shown that most ruptures occur at the first infarction (72%), after an average of 5.4 days of evolution 20 . The most commonly affected site is the lateral wall, as shown in the aforementioned series and also others in the lietarture 20,21 .…”
Section: Commentsmentioning
confidence: 99%
“…No association has been described between the size of the infarction and the risk of rupture; and it is not unusual for the infarction to be small. Data collected at the Laboratory of Pathology of the Heart Institute (InCor) 20 in cases of necropsy have shown that most ruptures occur at the first infarction (72%), after an average of 5.4 days of evolution 20 . The most commonly affected site is the lateral wall, as shown in the aforementioned series and also others in the lietarture 20,21 .…”
Section: Commentsmentioning
confidence: 99%